ANTIOXIDANT ACTIVITY OF CATECHINS ISOLATE OF UNCARIA GAMBIER ROXB IN MALE RATS - Musdja, Muhammad Yanis; Rahman, Hary Abdul; Hasan, Delina (LIFE: International Journal of Health and Life-Sciences, 2018)
The aims of this study were to determine the antioxidant activity of catechins isolates of gambir by measuring the levels of Malondialdehid (MDA) in male white rats. Methods: Catechins of gambir were isolated by using partition method with ethyl acetate solvent. Gambir quality was determined based on National Standard of Indonesia: SNI 01-3391-2000. The yield of catechins obtained from the gambir isolate was determined as (+)-catechins by comparing with standard (+)-catechins and measured by a spectrophotometer UV-VIS at wavelength 279 nm. A total of 25 male rats were divided into 5 groups. Administration of catechins was suspended in 0.5% Na CMC with dose of 5 mg/kg b.w, 10 mg/kg b.w and 20 mg/kg b.w, as positive control was used the suspension of vitamin E, 20 mg/kg b.w in Na-CMC 0.5% and as negative control was used 0.5% Na-CMC suspension. Administration of test preparations was performed per oral, 1 times per day for 7 days. On the eighth day, the rats were made become oxidative stress with swimming in water about 1 hour, until almost drowned. MDA levels of rats in each group were measured by comparing MDA levels, before were given test preparation on first day and after were given test preparations on the eighth day. The MDA level of serum rats were measured based on Wills method. Result: The statistical test of catechins isolate of gambir showed that all dosage of catechins isolate test of gambir had antioxidant effect and had significant difference to negative control (p <0.05). Doses 5 and 10 mg/kg b.w did not show significant differences with vitamin A as positive control, while Dose 20 mg/kg b.w gave the strongest antioxidant effect and had significant difference with positive control (p <0.05). Conclusion: Catechins of Gambir has stronger potential as an antioxidant than vitamin A.